Penggunaan Limbah Kulit Singkong pada Filter Air Sederhana Skala Rumah Tangga - Ihat Solihat; Agustina Dyah Setyowati (Jurnal Ilmiah Teknik Kimia, 2021)
Cassava (Manihot utillisima) is a staple food for Indonesians after rice and corn. Cassava is a natural product (product) which is abundant in Indonesia, especially in the areas of Central Tawa and West Java. Activated carbon is a porous material derived from carbon material by combustion or thermal decomposition. Activated carbon is widely used for water purification, medicine, waste treatment and as a filter in compressed air (Lam et al., 2017). The purpose of this research is the quality of activated charcoal from cassava peel absorption capacity of activated carbon from cassava peels as a water filter, especially for removal of Cu (II) metal with a variety of activators and the optimum duration of contact with the use of activated carbon in a simple home scale water filter. The results showed that the quality of activated charcoal from coffee grounds which includes the quality of yield, moisture content, ash content and absorption of iodine has met SNI No.06-3730- 1995 Activated Charcoal Quality Standards. The higher the concentration, the greater the absorption of activated charcoal on Cu (II) metal, and from the variation data the most optimal activator is activated charcoal with a KOH activator of 0.3 m. The results of boxing the activated charcoal within 5 hours with an average yield of 0.1898 mg per liter meet the clean water standards, namely according to the 2008 East Java Regional Regulation which states that the Cu content in water is at a threshold of 0.2 mg per liter.